STUDY OF THE INFLUENCE OF RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), EARNINGS PER SHARE (EPS), AND ECONOMIC VALUE ADDED (EVA) ON LQ45 STOCK RETURN ON THE INDONESIA STOCK EXCHANGE FOR 2017–2019 - Rofinus Leki (Jurnal Ilmiah Ekonomi Bisnis, 2021)
Abstract : This study aims to determine and examine the effect of the variable return on assets (ROA), return on equity (ROE), earnings per share (EPS), and economic value added (EVA) on stock returns of 25 LQ45 companies listed on the Stock Exchange. Indonesia in 2017 to 2019. The research data is processed quantitatively using the multiple linear regression analysis method with the SPSS version 21 program. The results show that return on assets (ROA), return on equity (ROE), earnings per share (EPS) ), and economic value added (EVA) has no partial or simultaneous effect on stock returns of 25 LQ45 company shares on the IDX in Jakarta in 2017 to 2019. The results of this study support some of the results of previous studies, but also contradict some of the results. previous research conducted by different researchers. Keywords : Return on assets, return on equity, earnings per share, economic value added, return saham.